2008
DOI: 10.1111/j.1365-277x.2008.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrient intakes of primary school children: a comparison of school meals and packed lunches

Abstract: Background New school meal standards are currently being phased in by the government in an attempt to improve the nutritional composition of school food. However, no standards are applied to packed lunches. The present study aimed to compare the food and nutrient intakes of primary school children eating a school meal with those taking a packed lunch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 5 publications
8
63
2
9
Order By: Relevance
“…In Japan, children at nursery facilities usually eat school lunches, while those at kindergartens usually bring packed lunches from home. There are no standards for ensuring that children bring healthy packed lunches in the UK (Rees, Richards & Gregory, 2008, Evans et al, 2010a where approximately half of the school pupils get packed lunch from home (Smithers et al, 2000) similar trends have been observed in Japan, and it seems that foods cooked by mothers are included in children's packed lunches. (Birch, 1979, Birch & Fisher, 1998; Vereeken and Maes (2010) reported that young children's dietary habits were associated with the mothers' nutritional knowledge and attitudes.…”
Section: Introductionmentioning
confidence: 87%
“…In Japan, children at nursery facilities usually eat school lunches, while those at kindergartens usually bring packed lunches from home. There are no standards for ensuring that children bring healthy packed lunches in the UK (Rees, Richards & Gregory, 2008, Evans et al, 2010a where approximately half of the school pupils get packed lunch from home (Smithers et al, 2000) similar trends have been observed in Japan, and it seems that foods cooked by mothers are included in children's packed lunches. (Birch, 1979, Birch & Fisher, 1998; Vereeken and Maes (2010) reported that young children's dietary habits were associated with the mothers' nutritional knowledge and attitudes.…”
Section: Introductionmentioning
confidence: 87%
“…However, public discussion on school meals and other forms of eating outside the home has increased during recent years, e.g. in the United Kingdom (8)(9)(10)(11)(12) . Even though there is a lack of international scientific research on catering services, there are several sources of nationally representative data in Finland that can be used to study eating patterns at schools and worksites.…”
Section: History Of School and Workite Meal Servicesmentioning
confidence: 99%
“…However, studies conducted before the introduction of the 2006 food-based standards found that packed lunches typically contained fewer fruit and vegetables and more sources of sugar, saturated fat and Na than school lunches (3)(4)(5) , although they often provided more Ca and Fe (6) . Packed lunches consumed by pupils from low-income households were typically of poorer nutritional quality (7) .…”
mentioning
confidence: 99%